One new species of the genus Alloteratura Hebard, 1922 (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China - Shi, Fu-Ming; Di, Juan-Xia; Chang, Yan-Lin (Zootaxa, 2014)
The paper describes one new species of the genus Alloteratura Hebard, 1922 from Yunnan, China, i.e. Alloteratura quaternispina, sp. nov.